Avaliação do conhecimento de pacientes submetidos à hemodiálise sobre potássio e fósforo - Chacón, Abby Branchini (My University, 2019)
Objective: To assess knowledge on potassium and phosphorus in patients undergoing hemodialysis and to associate with serum levels and other clinical variables. Methods: Cross-sectional study. Interviews were carried out in patients of both genders, above 18 years old, undergoing hemodialysis for at least three months, in Caxias do Sul- Brazil, at Hospital Geral (General Hospital), during the period of January to April 2019. The level of understanding regarding phosphorus and potassium was evaluated through a questionnaire developed and adapted based on previous studies. All participants have signed the Free Prior and Informed Consent. Results: 73 patients were interviewed between January and April 2019. The average number of correct answers was 9,78 ± 2,99. Regarding to potassium, an average of 6,75 ± 1,65 and to phosphorus of 4,64 ± 2,10. Positive correlation was found in specific knowledge of phosphorus and serum levels of this mineral (r = 0,305; p = 0,009), however not for potassium (r = 0,101; p = 0,395). The total number of correct answers and the values are positively correlated with schooling and negatively with age. Conclusion: The patients have demonstrated intermediate understanding regarding phosphorus and potassium, showing less knowledge on phosphorus and more on potassium. Patients with higher serum levels of phosphorus, have shown greater levels of knowledge regarding this mineral, while this association was not observed for potassium levels. The highest number of correct answers to the questionnaire was related to a higher schooling and younger age of the patients. [resumo fornecido pelo autor]
Objetivo: Avaliar o conhecimento sobre potássio e fósforo em pacientes submetidos à hemodiálise e associar com níveis séricos e outras variáveis clínicas. Métodos: Estudo transversal. Foram entrevistados pacientes de ambos os sexos, acima de 18 anos, submetidos à hemodiálise há pelo menos três meses, no Hospital Geral de Caxias do Sul-RS no período entre janeiro e abril de 2019. O nível de conhecimento relacionado a fósforo e potássio foi verificado através de um questionário desenvolvido e adaptado com base em estudos prévios. Todos os participantes assinaram o Termo de Consentimento Livre e Esclarecido. Resultados: Foram entrevistados 73 pacientes entre janeiro e abril de 2019. A média de acertos do questionário foi de 9,78 ± 2,99 acertos. Em relação aos acertos de potássio, a média foi de 6,75 ± 1,65 acertos e fósforo foi de 4,64 ± 2,10. Houve correlação positiva entre conhecimento específico de fósforo e níveis séricos deste mineral (r=0,305; p=0,009), porém não para potássio (r=0,101; p=0,395). O número total de acertos totais e específicos se correlacionou positivamente com escolaridade e negativamente com idade. Conclusão: Os pacientes demonstraram conhecimento intermediário em relação ao fósforo e potássio, sendo menor conhecimento sobre fósforo e maior sobre potássio. Pacientes com maiores níveis séricos de fósforo apresentaram maior conhecimento sobre este mineral, enquanto essa associação não foi observada para os níveis de potássio. Um maior número de acertos do questionário foi relacionado a maior escolaridade e menor idade dos pacientes. [resumo fornecido pelo autor]
Keywords: Hemodiálise; Conhecimento e aprendizagem; Potássio; Fósforo